THE EFFECTIVENESS OF USING AUDIO-VISUAL AIDS TO IMPROVE THE LISTENING SKILL OF SECOND YEAR SECONDARY STUDENTS AT THE INSTITUTE OF ISLAMIC EDUCATION AL-HADITH BAGAN BATU RIAU - Harahap, Muhammad Sapii; Nunzairina, Nunzairina; Isnawati, Isnawati; Subari, Zamiat (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The objectives of the research are: 1) to find out the efficiency of the listening skill in the tribal exam for second year secondary students at the Institute of Islamic Education Al-Hadith Al-Husna Pagan Batu Riau. 2) To find out the efficiency of the listening skill in the post-exam for second year secondary students at the Institute of Islamic Education Al-Hadith Al-Husna Pagan Batu Riau. 3) To find out the teaching procedure in upgrading the listening skill using audio-visual aids for the second year secondary students at the Institute of Islamic Education Al-Hadith Al-Husna Pagan Batu Riau. The research method used is Classroom Action Research (CAR) with the type of experiment. First, the researcher plans the teaching and learning process, and prepares materials on listening skills, then carries out the teaching and learning process in the classroom using audiovisual media. After that, the researcher observed the teaching and learning process that was running and then conducted an evaluation to measure students' abilities so that it became a benchmark in comparing test scores before and after the implementation of learning. The method for collecting data is by observation, interview and test. The results of the following class action research are in accordance with the results of the tests carried out on, 1) pre-cycle exam = 1,611 with an average of 67.13, first cycle test scores = 1,713 with an average of 71.38, second cycle test scores = 1,878 with an average of 78.25. 2) The score obtained by students makes researchers believe that an increase in listening skills in class XI B MAS Alhusna students can be obtained using audiovisual media because this method can focus students' concentration on the material being taught.